Influence of Field Work Practices, Work Motivation, and Communication Skills on Vocational School Students' Work Readiness - Deanda, Galeri Garnisha; Darmawan, Ilham Akbar; Irwanto, Irwanto (DPTE FT UNY, 2024)
Based on the latest data from the Serang Regency Central Statistics Agency in 2022, the Open Unemployment Rate (TPT) of Vocational High School (SMK) graduates is still relatively high compared to graduates of other levels of education, namely 12.87%. Apart from that, from the results of observations, there are still many vocational school students who still need to be ready for work. This is because the industrial internship program has not been able to optimize students' work readiness, students' work motivation still needs to be visible, and students' communication skills still need to be improved for their readiness to enter the world of work. This research seeks to determine the influence of industrial internship, work motivation, and communication skills on vocational school students' work readiness. This research uses a quantitative approach to answer the research hypothesis, which asks whether industrial internship, work motivation, and communication skills are positively correlated with vocational school students' work readiness. This research used a questionnaire distributed to 180 students in seven vocational schools in Serang Regency. This research proved that industrial internship, work motivation, and communication skills significantly influence work readiness (7%). For the conclusions and limitations of existing research, this research provides several suggestions for improving vocational school students' work readiness by paying more attention to the variables of industrial internship, work motivation, and communication skills.